SENGKETA PERPAJAKAN DALAM PERSPEKTIF KEKUASAAN KEHAKIMAN - Suyanto, Heru; Suherman, Suherman (Jurnal Yuridis, 2015)
The existence of the Tax Court has affirmed in UU No. 14 of 2002 on the Tax Court has the authority to examine and decide cases on tax disputes, but the presence of some of the characteristics of the Tax Court is not synergistic with the State Administrative Court still leaves will debate the status of the existence of the Court Tax system of judicial authority in Indonesia. Basically the Tax Court does have characteristics that almost resembles the State Administrative Court seen from the types of disputes that can be examined and decided upon. On the subject of dispute there is a slight difference due to the State Administrative Court only recognizes the people and civil legal entity that can take the case to be examined. While the Tax Court also acknowledged the permanent establishment as one of the subjects may submit the case to be examined in the Tax Court. It is not appropriate for some academics so as not fitting if the Tax Courtis under the State Administrative Court.